Community Involvement in Rural Entrepreneurship - Talib, Azlizan; Yusoff, Mohd Nazaruddin; Md Zan, Zainal (Universiti Islam Melaka, 2017)
Community‟s involvement plays a significant role in determining the success of a development program. In the context of the entrepreneurship, previous studies have been able to sample the evidence of the scarcity of this involvement. Factors like the difficulty of accepting change, the idiosyncrasies of the bureaucracy, financial issues, the shortage of training and courses, political frictions, the lack of response and support from the rural people and the like, are seen to leave an impact in influencing this public involvement. This research was conducted in the selected village of Gerakan Daya Wawasan (GDW) in the district of Kubang Pasu, Kedah namely Kampung Natoi and Kampung Tradisi Paya Pahlawan. The study findings have shown that the level of involvement of the rural residents in the entrepreneur fields is moderate. The factors identified to have influenced this level of involvement include capital/financial factor also the training and courses of entrepreneurship